Adrenocortical sensitivity, moderated by ongoing stress, predicts drinking intensity in alcohol-dependent men. (February 2017) - Adinoff, Bryon; Leonard, David; Price, Julianne; Javors, Martin A.; Walker, Robrina; Brown, E. Sherwood; Xiao, Hong; Rao, Uma
Highlights: Allostatic load from stress and cortisol secretion may worsen course of alcoholism. Effects of HPA axis activity and ongoing stress upon drinking severity were assessed. Life stress and drinking assessed biweekly for 6 months post-treatment discharge. Adrenocorticoid reactivity, moderated by stress, predicted drinking intensity. Addressing both glucocorticoid and stress reactivity may lessen relapse severity. Abstract: Allostatic load from both environmental stressors and persistent glucocorticoid secretion has been associated with disease severity in alcohol dependence. Heightened relapse risk and/or drinking severity, in particular, may be a reaction to alcohol- and withdrawal-induced changes in physiological stress response systems coupled with ongoing life stress, although their shared contributions upon drinking severity have not been assessed. To investigate the combined contribution of hypothalamic-pituitary-adrenal (HPA) reactivity and environmental stressors (e.g., ongoing life stress) to relapse severity in alcohol-dependent men following treatment, plasma adrenocorticotropin (ACTH) and cortisol were obtained in 4–6 weeks abstinent alcohol-dependent men (n = 41) following a psychosocial stressor [the Trier Social Stress Test (TSST)] and two pharmacological provocations [ovine corticotropin releasing factor (oCRH) and cosyntropin]. Following treatment discharge, drinking outcomes (primary outcome: drinks per drinking day (DDD); secondary outcomes: total drinks and drinking days) were assessed weekly and ongoing life stress was assessed biweekly for 24 weeks following treatment discharge. Generalized estimating equation models of drinking severity were fit with basal and stimulated ACTH and cortisol concentrations as predictors and ongoing life stress as the moderator. Greater levels of life stress were independently associated with greater drinking intensity (DDD and total drinks) but not frequency (days drinking). Higher basal cortisol:ACTH or provoked cortisol:ACTH ratios were strongly associated with greater post-treatment DDD in individuals who experienced higher levels of ongoing stress. In conclusion, ongoing life stress is associated with post-treatment drinking intensity in alcohol dependent men; stress also strengthens the relationship between adrenocortical sensitivity and post-treatment drinking. Physiological measures of allostatic load and environmental stressors conjointly increase relapse intensity.